2022
DOI: 10.1111/cen.14834
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and ultrasonic risk factors for high‐volume central lymph node metastasis in cN0 papillary thyroid microcarcinoma: A retrospective study and meta‐analysis

Abstract: Objective: Papillary thyroid microcarcinoma (PTMC) comprises more than 50% of all newly detected cases of papillary thyroid carcinoma (PTC). High-volume lymph node metastasis (involving >5 lymph nodes) (hv-LNM) is associated with PTMC recurrence. In half of the clinically node-negative (cN0) PTMC patients, central lymph node metastasis (CLNM) is pathologically present. However, clinical risk factors for high-volume CLNM (hv-CLNM) in cN0 PTMC have not been defined well.Therefore, we aimed to obtain evidence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Hence future studies could research the difference between contralateral and ipsilateral CLNM with BRAF mutation. CLNM is usually present in 17%–64% of patients with PTMC, and even in cN0 PTMC, up to 34.8% to 60.9% of patients develop CLNM 38 . Our analysis showed that cN0 PTMC with BRAF mutation were more likely to have CLNM (OR = 1.70, 95% CI: 1.40–2.07).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Hence future studies could research the difference between contralateral and ipsilateral CLNM with BRAF mutation. CLNM is usually present in 17%–64% of patients with PTMC, and even in cN0 PTMC, up to 34.8% to 60.9% of patients develop CLNM 38 . Our analysis showed that cN0 PTMC with BRAF mutation were more likely to have CLNM (OR = 1.70, 95% CI: 1.40–2.07).…”
Section: Discussionmentioning
confidence: 56%
“…CLNM is usually present in 17%-64% of patients with PTMC, and even in cN0 PTMC, up to 34.8% to 60.9% of patients develop CLNM. 38 Our analysis showed that cN0 PTMC with BRAF mutation were more likely to have CLNM (OR = 1.70, 95% CI:…”
Section: Resultsmentioning
confidence: 68%
“…In addition to the Rad score, age and capsule invasion were independent risk factors for CLNM. In most previous studies, younger age was closely correlated with a high incidence of CLNM irrespective of the threshold [ 12 , 21 – 22 ]. This may be explained by the negative association between age and PTMC promotion rate [ 23 ].…”
Section: Discussionmentioning
confidence: 85%
“…Screening patients at high preoperative risk of CLNM is crucial to determining the indications for PCLND [ 12 ]. Numerous studies have analyzed the risk factors for CLNM in patients with cN0 PTMC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the meta-analysis of Wang et al. ( 26 ) defined high-volume lymph node metastasis in PTC as involving >5 lymph nodes. At the same time, Huang et al.…”
Section: Discussionmentioning
confidence: 99%